INDONESIAN AUTHORS WRITING THEIR DISCUSSION SECTIONS BOTH IN ENGLISH AND INDONESIAN RESEARCH ARTICLES - Lulus Irawati; Ali Saukah; Suharmanto Ruslan (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The study aims to investigate how Indonesian authors write their English and Indonesian research article (RA) discussion sections. There were 7 Indonesian authors who write 1 English research article and 1 Indonesian research article published in national accredited journals. The study executed rhetorical moves designed by Swales (1990) to be used here as the instrument. In general, the findings show that 7 Indonesian authors operate not too different rhetorical patterns of English and Indonesian RA discussion sections viewed from moves occurrences, completeness, and order of the move structures. Nearly all 7 Indonesian authors show 5 moves in the English RA discussion section consisting of statement of the results-(un)expected outcome-reference to previous research-explanation-deduction and hypothesis. They use 6 moves in the Indonesian RA discussion section consisting of statement of the results-(un)expected outcome-reference to previous research-explanation-exemplification-deduction and hypothesis. However, each author has his/her specific move structure seen from the moves order and moves frequency. The specific uses of move structure are explained with examples in the forms of sentences or phrases. Thus, the authors are in the position of having their rhetorical patterns suited the context and communities.Keywords: Indonesian authors, research articles (RA), discussion sections, rhetorical patterns PILIHAN POLA RETORIKA PENULIS INDONESIA DALAM MENULIS BAGIAN PEMBAHASAN ARTIKEL PENELITIAN BERBAHASA INGGRIS DAN BERBAHASA INDONESIA Abstrak: Penelitian ini bertujuan untuk meneliti bagaimana penulis Indonesia menulis bagian pembahasan artikel penelitian berbahasa Inggris dan berbahasa Indonesia. Data diperoleh dari 7 penulis Indonesia yang pernah menulis dan mempublikasi 1 artikel penelitian berbahasa Inggris dan 1 artikel penelitian berbahasa Indonesia di jurnal ilmiah terakreditasi nasional. Penelitian ini menggunakan pola retorika (moves) yang dikembangkan oleh Swales (1990) sebagai instrumen untuk menganalisis bagian pembahasan artikel penelitian. Secara umum, hasil penelitian menunjukkan bahwa ketujuh penulis Indonesia memilih pola retorika yang tidak terlalu berbeda pada bagian pembahasan yang berbahasa Inggris dan berbahasa Indonesia, dilihat dari frekuensi kemunculan moves, kelengkapan moves, dan urutan movesnya. Sebagian besar penulis memilih 5 moves pada bagian pembahasan yang berbahasa Inggris, yaitu statement of the results-(un)expected outcome-reference to previous research-explanation-deduction and hypothesis. Bagian pembahasan yang berbahasa Indonesia memiliki 6 moves, yaitu statement of the results-(un)expected outcome-reference to previous research-explanation-exemplification-deduction and hypothesis. Walaupun begitu, setiap penulis memiliki pilihan moves tertentu dari segi urutan moves dan frekuensi kemunculannya. Dapat disimpulkan bahwa penulis-penulis Indonesia tersebut memilih pola retorikanya disesuaikan dengan konteks dan komunitas pembaca artikel penelitian di jurnal ilmiah yang mereka pilih.Kata Kunci: Penulis Indonesia, artikel penelitian (RA), bagian pembahasan, pola retorika